Hadis Moderasi Beragama dalam Pancasila sebagai Usaha Mewujudkan Bangsa yang Harmoni - Mohamad Barmawi; Muhammad Uzaer Damairi; Abdur Rahman W (Advances in Humanities and Contemporary Studies, 2022)
AbstractReligious moderation means maintaining a harmonious life together in a pluralistic life in which there are various differences. Pancasila as a philosophy in Indonesia is an effort made by the leaders to create a peaceful life in the frame of difference. This formulation was made because Indonesia is a country in which there are various differences, both in ethnicity, culture, language, and even beliefs. The population, who is predominantly Muslim, demands a formulation based on religion, so it is very possible that the formulations in the Pancasila points are in line with religious teachings.In a study that uses qualitative and literary methods, it aims to reveal the contribution of moderation traditions in the formulation of Pancasila as an effort to create a harmonious nation. And this study succeeded in making conclusion, that the formulations contained in the items of Pancasila are in accordance with the values ​​of the traditions regarding religious moderation.